Historical developments of financial rights after divorce in the Malaysian Islamic family law - Hasbullah@Abdullah, Muslihah; Mohd Zin, Najibah (Canadian Center of Science and Education, 2009)
Islamic family law plays a significant role in minimizing the unpleasant effects of the family break up faced by the divorced women and their children by protecting their rights to financial support after divorce. This study undertakes to discuss the historical development of the financial rights after divorce applicable among the Muslims in the pre and post colonial periods, particularly with reference to the iddah maintenance, mut’ah, arrears of maintenance, and child maintenance. The study indicates that despite the provisions were inconformity with the Islamic principles, the applications were restricted and influenced by the Shafi’i madhhab. However, the amount of iddah maintenance and mut’ah were substantial taking into account the standard of living of the Malay society in the 15th and 16th century. This means that the welfare of the divorced women was taken care of since the codification of the Islamic law and its implementation in the Malay society.